Fungi Isolated from Traditional and Exotic Apple Varieties from Portugal and Patulin Production - C.M.M. Almeida ,; M.M. Lopes, (Journal of Pharmacy and Nutrition Sciences, 2015)
The objective of our study was to examine the effects of cultivar type on developed fungi species and evaluate the potential for patulin production by fungi. In addition, patulin diffusion was also investigated. The experiments were carried out in traditional (Bravo de Esmolfe) and exotic apples (Golden, Starking, Fuji, Reineta Parda and Gala Galaxy) varieties from Portugal. High-performance liquid chromatography with solid phase extraction and UV detection (SPE-HPLC-UV) was validated and used to analyze patulin in the apple. The most prevalent fungal population was Penicillium spp and 27% of rotten fruits had patulin. Fungi of the genera Cladosporium spp., Alternaria spp., Fusarium spp. and Aspergillus spp. were also found even in apples without patulin production. The variety with the highest production of patulin was Bravo Esmolfe, however this variety showed the lowest prevalence of Penicillium spp. compared to other varieties of apples where was detected patulin. Patulin was not detected in any apples of Fuji and Gala varieties, despite having been identified fungi usually associated with the production of patulin. Thus, these two varieties are presented as the most suitable for the production of the apple based-foods.